2004
DOI: 10.1017/s1367943004001325
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inbreeding on mortality during a morbillivirus outbreak in the Mediterranean striped dolphin (Stenella coeruleoalba)

Abstract: Between 1990 and, Mediterranean striped dolphins (Stenella coeruleoalba) suffered high mortality due to a morbillivirus epidemic. Ten highly variable microsatellite markers were used to assess the population structure of a sample of these stranded animals and to assess the genetic consequences of the epizootic on present stocks. We found little evidence of population structure within the Mediterranean, but distinct separation between this and the North Sea (Atlantic) population, the latter also showing greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 42 publications
(41 reference statements)
5
51
1
Order By: Relevance
“…By implication, any individuals who are born to related parents are disproportionately likely to suffer lethal worm burdens, which in turn removes them from the population. This therefore agrees with earlier studies that suggested inbred individuals carry more parasites, a greater diversity of parasites and may provide a weak point through which new pathogens can enter the population (Coltman et al, 1999;Acevedo-Whitehouse et al, 2003;Valsecchi et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By implication, any individuals who are born to related parents are disproportionately likely to suffer lethal worm burdens, which in turn removes them from the population. This therefore agrees with earlier studies that suggested inbred individuals carry more parasites, a greater diversity of parasites and may provide a weak point through which new pathogens can enter the population (Coltman et al, 1999;Acevedo-Whitehouse et al, 2003;Valsecchi et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…In rehabilitating sea lions, all classes of sick animals revealed elevated homozygosity (AcevedoWhitehouse et al, 2003), whereas in studies of infectious disease, heterozygosity has been implicated separately in both viral (Valsecchi et al, 2004) and bacterial (Acevedo-Whitehouse et al, 2003) diseases, as well as influencing the strength of the innate immune response (Hawley et al, 2005). However, the exact mechanism underlying these correlations remains obscure (Hansson and Westerberg, 2002;Pemberton, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The abnormally high sea-surface temperatures (SSTs) and low rainfall conditions in the winter preceding the 1990-1992 outbreak in the western Mediterranean apparently depressed peak productivity that occurs each year in early spring and determines the regional abundance of fish (Aguilar & Raga 1993). This epidemic also started in regions containing unusually large numbers of inbred dolphins that were possibly more susceptible to diseases (Valsecchi et al 2004).…”
Section: Cetacean Morbillivirusmentioning
confidence: 99%
“…Empirical evidence for disease costs of inbreeding has been documented in captive settings (e.g. Spielman et al 2004;Hawley et al 2005;Ross-Gillespie et al 2007;Charpentier et al 2008;Ilmonen et al 2008) as well as in an array of free-living taxa, including California sea lions (Zalophus californianus; Acevedo- Whitehouse et al 2003), Mediterranean striped dolphins (Stenella coeruleoalba; Valsecchi et al 2004), Galapagos hawks (Buteo galapagoensis; Whiteman et al 2006), Soay sheep (Ovis aries; Coltman et al 1999), harbour seals (Phoca vitulina; Rijks et al 2008) and American crows (Corvus brachyrhynchos; Townsend et al 2009a). In some studies, however, the relationship between inbreeding and disease is unclear (e.g.…”
Section: Introductionmentioning
confidence: 99%